Aspek Hukum Pidana Dalam Persaingan Usaha Pasca UU Cipta Kerja No. 6 Tahun 2023 Dan Peraturan Pemerintah Nomor 44 Tahun 2021 Serta Perpres Nomor 100 Tahun 2024 tentang KPPU: Criminal Law Aspects in Business Competition Post Job Creation Law No. 6 of 2023 and Government Regulation Number 44 of 2021 and Presidential Regulation Number 100 of 2024 concerning KPPU - Munawir Lubis, Zaini; Panjaitan, Budi Sastra; Harahap, Arifuddin (Jurnal Ilmiah Penegakan Hukum, 2025)
This study aims to determine the development of criminal law aspects within the framework of business competition law in Indonesia after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of the Job Creation Law into Law, Government Regulation Number 44 of 2021, and Presidential Regulation Number 100 of 2024 concerning the Business Competition Supervisory Commission (KPPU). These regulatory reforms have brought significant changes to the competition law enforcement mechanism, especially in clarifying the position of criminal and administrative sanctions against business actors who engage in monopolistic practices and unfair business competition. This study examines the extent to which criminal norms in business competition law are accommodated in the latest regulations and their implications for the effectiveness of law enforcement by the KPPU. This study uses a normative juridical method with a statutory and conceptual approach. Data sources were obtained through literature studies of laws and regulations, legal literature, and relevant KPPU decisions. The analysis was carried out qualitatively to examine the appropriateness and effectiveness of the regulation and application of criminal sanctions within the framework of Indonesian business competition law. The results of the study show that although the enforcement of competition law is still dominated by administrative sanctions, strengthening the criminal aspect is needed as a form of deterrent effect and protection of a fair and healthy business climate.